1998
DOI: 10.1152/ajpcell.1998.275.6.c1409
|View full text |Cite
|
Sign up to set email alerts
|

G protein-dependent activation of smooth muscle eNOS via natriuretic peptide clearance receptor

Abstract: In gastrointestinal smooth muscle, the neuropeptides vasoactive intestinal peptide (VIP) and pituitary adenylate cyclase-activating polypeptide (PACAP) induce relaxation by interacting with VIP2/PACAP3receptors coupled via Gs to adenylyl cyclase and with distinct receptors coupled via Gi1 and/or Gi2 to a smooth muscle endothelial nitric oxide synthase (eNOS). The present study identifies the receptor as the single-transmembrane natriuretic peptide clearance receptor (NPR-C). RT-PCR and Northern analysis demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
97
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(105 citation statements)
references
References 30 publications
5
97
2
Order By: Relevance
“…The role of NOS in ANP-induced pump stimulation is supported by L-NAME and radicicol blocking stimulation and HSP90 reproducing it. To our knowledge, NPR-A is not coupled to a NOS/NO/sGC/HSP90-mediated pathway, whereas NPR-C is linked to activation of NOS and NO in noncardiac cells (1,5,26). The highly selective NPR-C ligand AP-811 (19,38) abolished ANP-induced pump stimulation, whereas the NPR-C agonist ANP (4 -23), in a concentration not expected to have any effect on NPR-A (19, 38), reproduced it.…”
Section: Discussionmentioning
confidence: 91%
“…The role of NOS in ANP-induced pump stimulation is supported by L-NAME and radicicol blocking stimulation and HSP90 reproducing it. To our knowledge, NPR-A is not coupled to a NOS/NO/sGC/HSP90-mediated pathway, whereas NPR-C is linked to activation of NOS and NO in noncardiac cells (1,5,26). The highly selective NPR-C ligand AP-811 (19,38) abolished ANP-induced pump stimulation, whereas the NPR-C agonist ANP (4 -23), in a concentration not expected to have any effect on NPR-A (19, 38), reproduced it.…”
Section: Discussionmentioning
confidence: 91%
“…Since previous work has demonstrated that NPR-B KO animals are normotensive (28), these observations as a whole provide convincing evidence that, physiologically, NPR-C is the primary receptor triggered by CNP to maintain vascular function and blood pressure. The thesis is supported by the acute vasodilator (29,30) and hypotensive (31)(32)(33)(34) responses to exogenous CNP and the emerging signaling role of G i -coupled NPR-C in various cell types (35)(36)(37)(38)(39). CNP also produced a concentration-dependent relaxation of human vessels that was abolished in the presence of the selective NPR-C antagonist M372049 (lead compound based on AP-811; gift of C. Veale, AstraZeneca) (25,40) and following precontraction mediated by high K + (which abrogates smooth muscle hyperpolarization; Figure 2L).…”
Section: Resultsmentioning
confidence: 99%
“…37,38,44,45 In addition, NPR-C activation by C-ANP 4-23 was also reported to activate eNOS in various tissues including smooth muscle. 33 We also examined whether C-ANP 4-23 -induced attenuation of BP in SHRs is attributed to its ability to augment the levels of eNOS and NO; however, in the present in vivo study, we demonstrate that C-ANP 4-23 treatment decreased the enhanced levels of NO and eNOS in kidney and attenuated further the decreased levels of eNOS and NO in VSMC and aorta from SHRs and suggest that C-ANP 4-23 -induced decreased BP may not involve NO and NO-stimulated cGMP pathway. Furthermore, our results showing that the levels of ONOO − and nitrotyrosine were increased in VSMC, aorta, and kidney from SHRs that may be formed by the reaction of NO with O 2 − are in accordance with the studies of other investigators who have also reported an increased levels of ONOO − and nitrotyrosine content in aorta and mesenteric arteries as well as in kidney from SHRs without and with typical symptoms of metabolic syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…NPR-C activation by C-ANP [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] has been shown to activate NO synthase in various tissues including smooth muscle 33,34 resulting in the increased levels of NO that through cGMP contribute to BP regulation. Because SHRs have been shown to exhibit decreased expression of eNOS, 35 it was of interest to examine whether C-ANP 4-23 -induced decreased BP in SHRs is also attributed to its ability to augment the expression of eNOS.…”
Section: Effect Of In Vivo C-anp 4-23 Treatment On the Levels Of Enosmentioning
confidence: 99%